A new species group and species of the genus Pavania (Acari: Dolichocybidae), phoretic on Onthophagus vitulus (Coleoptera: Scarabaeidae) from Iran - Loghmani, Amir; Hajiqanbar, Hamidreza; Talebi, Ali Asghar (Zootaxa, 2013)
Pavania setiformis Loghmani & Hajiqanbar sp. nov. (Acari: Heterostigmatina: Dolichocybidae) associated with Onthophagus (Palaeonthophagus) vitulus (Fabricius) (Coleoptera: Scarabaeidae) is described from northeastern Iran. This remarkable new species represents a new setiformis species group characterized by seta-like sc1, instead of capitate trichobothria. The genus Pavania is thus divided into three species groups: the fusiformis group (15 species), the gymnopleuri group (3 species) and the setiformis group (1 species). We also found P. sabzevarensis Hajiqanbar & Khaustov, 2010 and P. onthophagi Hajiqanbar & Khaustov, 2010 phoretic on Gymnopleurus mopsus (Pallas) and Onthophagus (Euonthophagus) amyntas alces (Fabricius), respectively.